METHODES FOR EVALUATION OF ENVIRONMENTAL SUSTAINABILITY ON AGRICULTURAL HOLDINGS - Subić, Jonel; Popović, Vesna Ž.; Cvijanović, Drago V. (Economics of Agriculture, 2006)
The main scope of this work is to illustrate models in which sustainable farm development could be measured, accentuated primary on ecological function of agriculture. In order to be oriented to sustainable agriculture, certain changes in production and consumption of agricultural and food products are necessary. Reorientation from intensive agricultural production to, more environmentally friendly, multifunctional agriculture is of great importance in those circumstances. One of main principles of maintaining and strengthening the role of multifunctional agriculture is the access to the variety of methods for agricultural holdings development. In that sense, in the purpose of adoption decisions concerning efficiency of environmental protection and improvement, special micromodels are elaborated to evaluate environmental sustainability on farms.